Forsythiaside B ameliorates coagulopathies in a rat model of sepsis through inhibition of the formation of PAD4-dependent neutrophil extracellular traps - He, Wenju; Xi, Qiang; Cui, Huantian; Zhang, Pingping; Huang, Rui; Wang, Taihuan; Wang, Dongqiang (Frontiers in Pharmacology, 2022)
Forsythiaside B (FTB) is one of the main components of Forsythia suspensa (Thunb.) Vahl and exerts anti-inflammatory and anti-oxidative effects. However, its mechanism of action as a treatment for sepsis remains unclear. In this study, we developed a rat model of sepsis using cecal ligation and puncture (CLP) to investigate the effects of FTB on sepsis-associated coagulopathies. Using rats with sepsis, we investigated the effects of FTB on neutrophil extracellular trap (NETs) formation and peptidylarginine deiminase 4 (PAD4) expression in neutrophils. NET (DNase1) and PAD4 (Cl-amidine) inhibitors were used to further investigate whether FTB mitigates sepsis-associated coagulopathies by inhibiting PAD4-dependent NETs production. Our results showed that treatment with FTB increased the survival rate, ameliorated the CLP-induced inflammatory response and multiple organ dysfunction, and reduced CLP-induced pathological changes. FTB also alleviated the associated coagulopathies. Additionally, we demonstrated that treatment with FTB inhibited NETs formation and downregulated PAD4 expression in peripheral neutrophils. The effects of FTB on coagulopathies were similar to those of monotherapy with NET or PAD4 inhibitors. In conclusion, our study confirmed that FTB can alleviate coagulopathies in rats with sepsis. The underlying mechanism of FTB’s effect consists in inhibition of PAD4-dependent NETs formation.